2015
DOI: 10.1021/jacs.5b03284
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Switching of a Foldamer in a Multicomponent System by pH-Filtered Selection between Competing Noncovalent Interactions

Abstract: Biomolecular systems are able to respond to their chemical environment through reversible, selective, noncovalent intermolecular interactions. Typically, these interactions induce conformational changes that initiate a signaling cascade, allowing the regulation of biochemical pathways. In this work, we describe an artificial molecular system that mimics this ability to translate selective noncovalent interactions into reversible conformational changes. An achiral but helical foldamer carrying a basic binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 104 publications
0
42
0
1
Order By: Relevance
“…Synthetic molecules have been designed that have functional analogy with ligand-activated GPCRs like the β2 adrenoreceptor, 1 but they work only in organic solvents. [13][14][15][16] Results and Discussion Design of the receptor mimic. We set out to design and construct a synthetic molecular structure exhibiting the 'minimal' essential design features required for a functional mimic of a ligand-activated GPCR.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic molecules have been designed that have functional analogy with ligand-activated GPCRs like the β2 adrenoreceptor, 1 but they work only in organic solvents. [13][14][15][16] Results and Discussion Design of the receptor mimic. We set out to design and construct a synthetic molecular structure exhibiting the 'minimal' essential design features required for a functional mimic of a ligand-activated GPCR.…”
mentioning
confidence: 99%
“…19 In solution, these "foldamers" 20 populate almost exclusively 21 two rapidly exchanging conformational states of left or right handed helical screw sense, with the relative population of these two states being remarkably sensitive to chiral influences. [22][23][24][25] A chiral ligand covalently 15 or non-covalently 16 bound to one terminus of an Aib foldamer will propagate its conformational influence through the entire foldamer length. 26 In this way endto-end transmission of binding information over multi-nanometre distances has been accomplished through Aib foldamers dissolved in organic solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[162][163][164][165][166][167][168][169][170] In ab id to achievet his type of signalling using an artificial receptor,W ebb and Clayden initially demonstrated that a chiral ligand interacting with an aminoisobutyric acid (Aib) helical foldamer could induce overall changes in the handedness of the helix, therebyc ommunicating as ignal over several nanometers ( Figure 5D). [171][172][173] Following up on this work, this team modified one terminus of the helical foldamer with a photo-responsive azobenzene motif. Upon insertion into a membrane, they illustrated that the light-induced switching of the helical handedness couldb ep ropagated across ab ilay-er.…”
Section: Receptor Oligomerisationmentioning
confidence: 99%
“…Artificial receptors.A)First artificial bilayer signalling system. [171][172][173] E) Transmembrane signal transduction by translocationisa chieved through ar eceptor that is too shorttos pan the bilayer.Ani nput signal allows the receptor to migrate to the other side of the bilayer,w here secondaryreactions can take place. [153] B) Receptor dimerisation due to ligandb inding occurs by copper(II) coordinationt od ansyl ethylenediaminer eceptor moieties.…”
Section: Receptor Oligomerisationmentioning
confidence: 99%